Substance P and Calcitonin Gene Related Peptide Mediate Pain in Chronic Pancreatitis and Their Expression is Driven by Nerve Growth Factor - Liu, LianSheng; Shenoy, Mohan; Pasricha, Pankaj Jay (JOP. Journal of the Pancreas, 2011)
Context Calcitonin gene-related peptide (CGRP), substance P and nerve growth factor play an important role in inflammatory pain in various somatic pain models but their role in chronic pancreatitis has not been well studied. Objectives The aim of this study was to investigate the effects of intrathecal administration of calcitonin gene-related peptide antagonist and substance P receptor antagonist on pain behavior in a rat model of chronic pancreatitis and to determine whether nerve growth factor drives the up-regulation of expression of these neuropeptides in sensory neurons. Methods Pancreatitis was induced by retrograde infusion of trinitobenzene sulfonic acid into the pancreatic duct of adult rats. Three weeks post infusion continuous intrathecal infusion of the calcitonin gene-related peptide antagonist alpha CGRP8-37 or neurokinin-1 receptor antagonist CP-96345 or its inactive enantiomer CP-96344 was administered for seven days. The effects of treatment on pancreatic hyperalgesia were assessed by sensitivity of the abdominal wall to von Frey filament probing as well as by the nocifensive response to electrical stimulation of the pancreas. In a separate experiment chronic pancreatitis was induced and pancreas specific dorsal root ganglion neurons labeled with DiI were assessed for calcitonin gene-related peptide and substance P immunoreactivity. Results Intrathecal infusion of calcitonin gene-related peptide and neurokinin-1 receptor antagonists significantly attenuated behavioral pain responses in rats with chronic pancreatitis. Further, treatment of chronic pancreatitis rats with nerve growth factor antibody significantly reduced pancreas specific neurons expressing calcitonin gene-related peptide and substance P in thoracic dorsal root ganglion. Conclusions Calcitonin gene-related peptide and substance P mediate pancreatic hyperalgesia in chronic pancreatitis and nerve growth factor in turn sustains the up-regulation of these neuropeptides in pancreatic sensory neurons. Image: Anti-NGF treatment results in downregulation of substance P and CGRP.